Singing Styles - Jane Beethoven; Rosanne Emery; Cliff Lenz (Music magic video library, 1991)
Viewers see and hear many different styles of singing - -Enjoy various styles of singing, including jazz, barbershop, country, and gospel - - Hear renowned folk, pop, and country stars - -Discover differences between trained and untrained voices.